Nuclear Import of HIV-1 - Qi Shen (MDPI AG, 2021)
The delivery of the HIV-1 genome into the nucleus is an indispensable step in retroviral infection of non-dividing cells, but the mechanism of HIV-1 nuclear import has been a longstanding debate due to controversial experimental evidence. It was commonly believed that the HIV-1 capsid would need to disassemble (uncoat) in the cytosol before nuclear import because the capsid is larger than the central channel of nuclear pore complexes (NPCs); however, increasing evidence demonstrates that intact, or nearly intact, HIV-1 capsid passes through the NPC to enter the nucleus. With the protection of the capsid, the HIV-1 core completes reverse transcription in the nucleus and is translocated to the integration site. Uncoating occurs while, or after, the viral genome is released near the integration site. These independent discoveries reveal a compelling new paradigm of this important step of the HIV-1 life cycle. In this review, we summarize the recent studies related to HIV-1 nuclear import, highlighting the spatial–temporal relationship between the nuclear entry of the virus core, reverse transcription, and capsid uncoating.